Doctoral education, advanced practice and research: An analysis by nurse leaders from countries within the six WHO regions - Kim Mi Ja; McKenna Hugh; Davidson Patricia; Leino-Kilpi Helena; Baumann Andrea; Klopper Hester; Al-Gasseer Naeema; Kunaviktikul Wipada; Sharma Suresh K.; Ventura Carla; Lee Taewha (Elsevier B.V., 2025)
Doctoral education, advanced practice and research are key elements that have shaped the advancement of nursing. Their impact is augmented when they are integrated and synergistic. To date, no publications have examined these elements holistically or through an international lens. Like a three-legged stool they are inter-reliant and interdependent. Research is integral to doctoral education and influential in informing best practice. This significance and originality of this discussion paper stem from an analysis of these three topics, their history, current status and associated challenges. It is undertaken by renowned leaders in 11 countries within the six World Health Organisation (WHO) regions: South Africa, Egypt, Finland, United Kingdom, Brazil, Canada, United States, India, Thailand, Australia, and the Republic of Korea. The first two authors used a purposive approach to identify nine recognized nurse leaders in each of the six WHO regions. These individuals have presented and published papers on one or more of the three topics. They have led, or currently lead, large strategic organisations in their countries or elsewhere. All these accomplished scholars agreed to collect relevant data and contribute to the analysis as co-authors. Doctoral education has played a pivotal role in advancing nurse scholarship. Many Doctor of Philosophy (PhD) prepared nurses become faculty who go on to educate and guide future nurse researchers. They generate the evidence base for nursing practice, which contributes to improved health outcomes. In this paper, the development of nursing doctoral programmes is examined. Furthermore, PhDs and professional doctorates, including the Doctor of Nursing Practice, are discussed, and trends, challenges and recommendations are presented. The increasing number of advanced practice nurses worldwide contributes to better health outcomes. Nonetheless, this paper shows that the role remains absent or underdeveloped in many countries. Moreover, role ambiguity and role confusion are commonplace and heterogeneity in definitions and titles, and regulatory and legislatorial inconsistencies limit the role's acceptance and adoption. Globally, nursing research studies continue to increase in number and quality, and nurse researchers are becoming partners and leaders in interdisciplinary investigations. Nonetheless, this paper highlights poor investment in nursing research and a lack of reliable data on the number and amount of funding obtained by nurse researchers. The recommendations offered in this paper aim to address the challenges identified. They have significant implications for policy makers, government legislators and nurse leaders.